Viability Analysis of Ubungo II Gas Power Plant Efficiency Improvement Using Co-generation System - Nyanda, Elias E.; Mushi, Aviti T.; Justo, Jackson J. (Tanzania Journal of Engineering and Technology, 2022)
The power utility, Tanzania Electric Supply Company Limited (TANESCO) is faced with challenges of supplying adequate power to the ever-increasing demand. To this end, this paper explores the installed Ubungo Gas Power Plant (UGP II) located in Dar es Salaam to find means of utilizing it in co-generation method. The study embarked on detailed modelling of the system and run simulations which indicated that the co-generation can result to power generation efficiency increase between 10.42 to 50.92%. It is recommended to change the UGP II to exploit this co-generation method. Further, the study could be improved by including more parameters of the gas and steam plant and verify them experimentally. Keywords: Co-generation system, Gas turbine control system, System efficiency, Heat balance.